2021
DOI: 10.3389/fgene.2021.609657
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analyses of Splicing and Expression Quantitative Trait Loci Identified Susceptibility Genes of Glioma

Abstract: BackgroundThe functions of most glioma risk alleles are unknown. Very few studies had evaluated expression quantitative trait loci (eQTL), and insights of susceptibility genes were limited due to scarcity of available brain tissues. Moreover, no prior study had examined the effect of glioma risk alleles on alternative RNA splicing.ObjectiveThis study explored splicing quantitative trait loci (sQTL) as molecular QTL and improved the power of QTL mapping through meta-analyses of both cis eQTL and sQTL.MethodsWe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Here we explore two major heritable mechanisms of transcriptional regulation and modification, expression-quantitative trait loci (eQTLs) and splicing-QTL (sQTLs), to elucidate the molecular basis of ecological speciation. Since transcription has substantial genetic control, eQTL, and sQTL mapping provides information about genetic variants with modular effects on gene expression ( Carroll et al 2005 ; Wittkopp and Kalay 2012 ; Ishikawa et al 2017 ; Verta and Jones 2019 ; Leal-Gutiérrez et al 2020 ; Kerimov et al 2021 ; Patro et al 2021 ), which are useful for understanding the genomic architecture and evolution of complex traits. Both eQTLs and sQTLs can be classified into cis (local) and trans (distant) effects.…”
Section: Introductionmentioning
confidence: 99%
“…Here we explore two major heritable mechanisms of transcriptional regulation and modification, expression-quantitative trait loci (eQTLs) and splicing-QTL (sQTLs), to elucidate the molecular basis of ecological speciation. Since transcription has substantial genetic control, eQTL, and sQTL mapping provides information about genetic variants with modular effects on gene expression ( Carroll et al 2005 ; Wittkopp and Kalay 2012 ; Ishikawa et al 2017 ; Verta and Jones 2019 ; Leal-Gutiérrez et al 2020 ; Kerimov et al 2021 ; Patro et al 2021 ), which are useful for understanding the genomic architecture and evolution of complex traits. Both eQTLs and sQTLs can be classified into cis (local) and trans (distant) effects.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs associated with spliced RNA are mostly found within the binding sites for RNA‐binding proteins (RBPs), which may alter the ability of RBPs to bind and interact with pre‐mRNA and other RBPs within a spliceosome. 91 A functional SNP on the 20q13.33 region in linkage disequilibrium with another SNP mapped to intron 14 of RTEL1 affects the activity of an enhancer on 20q13.33 that leads to modulated expression of multiple genes implicated in glioma risks, including RTEL1 . RTEL1 expression is modulated by this SNP in isocitrate dehydrogenase I wild‐type glioma and during early brain development but not in normal adult brain tissues.…”
Section: Rtel1 Over‐expression/activity Promotes Tumorigen...mentioning
confidence: 99%
“…The 20q13.33 genomic region including RTEL1 may mediate its risk effect in gliomagenesis by regulating the transcriptome through its multiple alternatively spliced transcripts such as exome skipping. SNPs associated with spliced RNA are mostly found within the binding sites for RNA‐binding proteins (RBPs), which may alter the ability of RBPs to bind and interact with pre‐mRNA and other RBPs within a spliceosome 91 . A functional SNP on the 20q13.33 region in linkage disequilibrium with another SNP mapped to intron 14 of RTEL1 affects the activity of an enhancer on 20q13.33 that leads to modulated expression of multiple genes implicated in glioma risks, including RTEL1 .…”
Section: Rtel1 Over‐expression/activity Promotes Tumorigenesismentioning
confidence: 99%
“…Traditionally, investigators have used expression quantitative trait loci (eQTL) or alternative splicing quantitative trait loci to explain molecular mechanisms [ 16 17 ] . Studies demonstrated that genetic variants correlated with APA were associated with the development of multiple diseases by altering the transcript length in the 3′ UTR of the gene [ 18 ] .…”
Section: Introductionmentioning
confidence: 99%